2003
DOI: 10.1063/1.1564883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spacer thickness on optical properties of stacked Ge/Si quantum dots grown by chemical vapor deposition

Abstract: Photoluminescence investigations on stacked Ge/Si dots with different spacer thicknesses are presented. According to the emission energy shift in the Ge dots, we found that a thinner spacer layer will lead to remarkable Ge–Si intermixing during the stacking of the Ge/Si dots. Such material intermixing not only shallows the dot potential depth, but also softens the sharpness of the dot/spacer interface. In addition, the temperature of photoluminescence quenching also varies with the spacer thickness. Finally, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The previous experimental findings revealed that the areal density, size uniformity, and spatial distribution of the SiGe islands grown via the Stranski-Krastanov (S-K) mode play an important role in controlling the luminescence properties of lasers and the detected wavelength of infrared photodetectors [1,3,4]. Different recipes have been proposed to enhance the island density, i.e., the boron (B) or carbon (C)-induced growth [5,6] and the low-temperature growth [7], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The previous experimental findings revealed that the areal density, size uniformity, and spatial distribution of the SiGe islands grown via the Stranski-Krastanov (S-K) mode play an important role in controlling the luminescence properties of lasers and the detected wavelength of infrared photodetectors [1,3,4]. Different recipes have been proposed to enhance the island density, i.e., the boron (B) or carbon (C)-induced growth [5,6] and the low-temperature growth [7], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the growth temperature, the thickness of the Si spacer layer (d Si ) in multilayer structures is the other parameter affecting the localization of the charge carriers in structures with Ge(Si) islands and their probability of radiative recombination [6,29,30]. On one hand, the increase of the Si spacer thickness leads to the decrease of elastic strain in the multilayer structure.…”
Section: Electroluminescence and Photoconductivity Of Structures Withmentioning
confidence: 99%
“…This effect has been described theoretically in Refs. [19][20][21]23, and 24 as well as demonstrated by many growth experiments; 1,2,22,25,26 however, it has not been measured or shown directly so far.…”
mentioning
confidence: 91%
“…Investigation of deformations and strain fields in silicon matrix structures embedded with vertically stacked Ge(Si) self-assembled islands D. A. Pavlov, 1,a) A. I. Bobrov, 1 A. V. Novikov, 2 D. S. Sorokin, 1 N. V. Malekhonova, 1 A. V. Pirogov, 1 D. E. Nikolitchev, 1 The information on the distribution of distortions and strains in GeSi heteronanosystems is fundamentally important for their design and creation. Studies in this field use a number of techniques, [1][2][3][4][5][6][7][8][9] among which one of the most informative is the cross-section high resolution transmission electron microscopy (HRTEM).…”
mentioning
confidence: 99%
See 1 more Smart Citation